The Role of Histopathological Outcome on Pain of Transrectal Ultrasound Guided Prostate Biopsy: A Randomised Trial - Ozah, Ehiremhen; Ezenwa, Ekene Victor (International Journal of Innovative Research in Medical Science, 2023)
Introduction: Transrectal ultrasound guided prostate biopsy is the gold standard for diagnosis of carcinoma of the prostate. The pain of prostate biopsy is of immense challenge. Many factors have been ascribed to it. Identifying such risk factors will assist in mitigating the pain associated with this procedure. This study therefore aims to assess the role of histopathological outcome on pain of TRUS guided prostate biopsy. Methods: The study was a prospective randomized study carried out in University of Benin Teaching Hospital over a 1year period between 2017 and 2018. Consecutive patients who met indications for biopsy were randomized into Group A: intrarectal xylocaine gel group and Group B: periprostatic block group. Pain was assessed during probe insertion, biopsy and one hour post biopsy using an 11-point visual analogue scale. Association between mean pain scores and histological diagnosis in both groups was assessed using the independent t- test, association between use of intrarectal xylocain gel, periprostatic block was done using the independent t-test. Level of significance set at p <0.05. Results: There was no statistically significant difference in mean pain score during probe insertion, biopsy and post biopsy (p=0.3888), (p=0.089) and (p=0.584) respectively between benign and malignant histological diagnosis for Group A, while there was also no statistically significant difference in mean pain score during probe insertion, biopsy and post biopsy (p=0.266), (p=0.506) and (p=0.522) respectively between benign and malignant histological diagnosis in Group B. Cancer detection rate for Group A and Group B was 64.3% and 59.1% respectively, which was not statistically significant p=0.662. Conclusions: The study demonstrated that pain of TRUS guided prostate biopsy is not influenced by histopathological outcome irrespective of mode of anaesthesia. Cancer detection rate was also not influenced by choice of anaesthesia during TRUS guided prostate biopsy.